Impact of Interferon-α Receptor-1 Promoter Polymorphisms on the Transcriptome of the Hepatitis B Virus-Associated Hepatocellular Carcinoma - Karamitros, Timokratis; Papatheodoridis, George; Paraskevis, Dimitrios; Hatzakis, Angelos; Mbisa, Jean L.; Georgopoulou, Urania; Klenerman, Paul; Magiorkinis, Gkikas (Frontiers in Immunology, 2018)
Background and aims Genetic polymorphisms within the promoter of interferon-α receptor type-1 (IFNAR1) have been associated with the susceptibility to and the outcome of chronic hepatitis B virus (HBV) infection. However, the impact of these polymorphisms in the transcriptome of the HBV-associated hepatocellular carcinoma (HCC) remains largely unexplored. Methods Using whole-genome and exome sequencing data from The Cancer Genome Atlas project, we characterized three single-nucleotide polymorphisms (SNPs: −568G/C, −408C/T, −3C/T) and one variable number tandem repeat [VNTR: −77(GT)n] within the IFNAR1 promoter sequence in 49 HCC patients. RNAseq data from 10 genotyped HCC samples were grouped according to their −77VNTR or −3SNP genotype to evaluate the impact of these polymorphisms on the differential expression on the HCC transcriptome. Results There is a fourfold higher impact of the −77VNTR on the HCC transcriptome compared to the −3SNP (q < 0.1, p < 0.001). The expression of the primary IFNAR1 transcript is not affected by these polymorphisms but a secondary, HCC-specific transcript is expressed only in homozygous −77VNTR ≤8/≤8(GT)n samples (p < 0.05). At the same time, patients carrying at least one −77VNTR >8(GT) allele, presented a strong upregulation of the fibronectin-1 (FN-1) gene, which has been associated with the development of HCC. Gene Ontology and pathway enrichment analysis of the differentially expressed genes revealed a strong disruption of the PI3K–AKT signaling pathway, which can be partially triggered by the extracellular matrix FN-1. Conclusion The IFNAR-1 promoter polymorphisms are not involved in the expression levels of the main IFNAR-1 transcript. The −77VNTR has a regulatory role on the expression of a secondary, truncated, HCC-specific transcript, which in turn coincides with disruptions in cancer-associated pathways and in FN-1 expression modifications.